An exploratory study of gait and functional outcomes after neuroprosthesis use in children with hemiplegic cerebral palsy. Issue 22 (23rd October 2017) - Bailes, Amy F.; Caldwell, Cailee; Clay, Mike; Tremper, Melissa; Dunning, Kari; Long, Jason
Abstract: Purpose: To evaluate the immediate orthotic, total and therapeutic effects of functional electrical stimulation (FES) neuroprosthesis use on clinic based measures of gait and function in children with hemiplegic cerebral palsy. Methods: Eleven children (mean 9 years 11 months) participated in an FES neuroprosthesis (Ness L300) intervention (4 week accommodation period followed by 12 weeks of daily use) and were assessed at baseline and post in stimulation off and stimulation on conditions. Measures included clinic based outcomes of gait and function. Results: No significant immediate orthotic effects were observed. Significant ( p < 0.01) total effects were noted for dorsiflexion at initial contact, Six-Minute Walk Test (6MWT), and walking speed. A significant therapeutic effect was found for steps off path on the Standardized Walking Obstacle Course (SWOC). Conclusions: Results support previous findings of neuroprosthesis total effects on gait and provide some evidence for effects on function. Therapeutic effects remain unclear. Implications for Rehabilitation: In this study, children with hemiplegic CP did not demonstrate immediate improvements in gait or function at their first clinic visit using the FES neuroprosthesis device suggesting one visit using the device is not sufficient to determine potential benefits. Over time with daily use of the FES neuroprosthesis, ankle dorsiflexion in swing and at initial contact, walking speed and endurance increased with the device worn. Overtime, no carryover effects in ankle dorsiflexion in swing and at initial contact were noted at the end of the intervention period with the device off. Clinicians should consider purchasing units to loan or rent to individuals to trial a device at home before determining long-term potential for benefit.